Design and Implementation of a Non-Invasive Brain Computer Interface for Prosthetic ARM - Pawar, Bhavesh; Mungla, Mitesh (Vietnam Journal of Science and Technology, 2025)
In the field of healthcare and assistive technology, brain-controlled prosthetic arms have emerged as a transformative innovation, instilling optimism among individuals with limb disabilities. This research unveils the successful development of a non-invasive brain-controlled prosthetic arm system, integrating the Emotiv EPOC X 14-channel brain sensor with 3D printing technology. This system effectively translates neural signals into precise movements, granting users a heightened level of control and functionality.The comprehensive methodology delineates the entire process, from the strategic placement of the brain sensor to data acquisition, processing, and servo control. Calibration and user training further refine system accuracy and responsiveness.Results affirm exceptional performance, boasting a remarkable 98.73% accuracy rate. Response times exhibit variations, contingent upon command intricacy and processing overhead. User feedback extols the system’s user-friendliness and its potential to bring about transformative change in daily life.The ensuing discussion delves into pivotal aspects of user comfort, long-term usability, and streamlined setup, all crucial elements of the user experience.This research serves as a prime example of interdisciplinary collaboration, unifying neuroscience, engineering, and ethical considerations, resulting in a pioneering assistive technology. The brain-controlled prosthetic arm not only signifies technological advancement but also embodies inclusivity and ethical responsibility.In conclusion, this research illuminates the profound potential of brain-controlled prosthetic arms, empowering individuals with limb disabilities, restoring autonomy, and bridging the gap between ability and disability. As technology advances, the horizon expands, ushering in a future where limitations fade, and aspirations are realized.